Health shock, medical insurance and financial asset allocation: Evidence from CHFS in China - Yaxuan Liu; Hao Yu; Zhi-Nan Lu (Health Economics Review, 2022)
Background: As health care cost is taking an increasingly substantial proportion of national wealth, health shocks and the subsequent medical expenditures have become increasingly vital contributions to fnancial risks. However, the individual or combined efects of social and fnancial medical insurance on household fnancial behaviors are poorly understood. This research aims to examine the efect of health shocks on fnancial asset mobility and portfolio allocation of the household. Also, whether medical insurance positively afects the fnancial market will be analyzed. Methods: Linear-regression models are used to determine the relationship between health shock, medical insurance, and household fnancial behaviors, including liquidity measures and fnancial portfolio (risk and risk-free assets). Two types of variables (transition probability and upward mobility) are constructed to measure the aggregate-level fnancial asset mobility. The portfolio of fnancial assets is categorized according to the risk it bears. Results: Households which experience health shocks are found to exhibit lower transition probability and upward mobility of fnancial assets than households that do not, and health shocks pose a more serious threat to lowincome households. From the inter-temporal perspective, households that have medical insurance exhibit a higher probability of raising their position within the national fnancial asset distribution, and are more inclined to invest in the risky fnancial assets. Commercial insurance displays a larger marginal efect on fnancial asset allocation than social insurance. Our study results highlight an essential link between health shocks, medical insurance, and household fnancial behavior. Conclusion: This work identifed and described the relationship between health-related factors (health shock and two types of medical insurance) and household fnancial behaviors (risky investment involvement and class mobility in fnancial asset). A strong link exists between the health and fnancial market, with heterogenous efects between urban and rural groups, households with distinct income levels, etc. A multilayered insurance system would be helpful to facilitate household income, fnancial consumption, and economic growth.
Keywords: 330; Health shock; Medical insurance; Financial asset allocation; Financial asset mobility; China